Human β-defensin-3 correlates with muscle fibre degeneration in idiopathic inflammatory myopathies. Issue 1 (February 2014) - Güttsches, Anne-Katrin; Jacobsen, Frank; Theiss, Carsten; Rittig, Andrea; Rehimi, Rizwan; Kley, Rudolf A; Vorgerd, Matthias; Steinstraesser, Lars
Sporadic inclusion body myositis (sIBM) and polymyositis (PM) are characterized by muscle inflammation, with sIBM showing additional degenerative alterations. In this study we investigated human beta defensins and associated TLRs to elucidate the role of the innate immune system in idiopathic inflammatory myopathies (IIM), and its association with inflammatory and degenerative alterations. Expression levels of human beta-defensin (HBD)-1, HBD-2, HBD-3 and TLR2, 3, 4, 7 and 9 were analysed by quantitative real-time PCR in skeletal muscle tissue. Localization of HBD-3, collagen 6, dystrophin, CD8-positive T-cells, CD-68-positive macrophages, β-amyloid, the autophagy marker LC3, and TLR3 were detected by immunofluorescence and co-localization was quantified. HBD-3 and all TLRs except for TLR9 were overexpressed in both IIM with significant overexpression of TLR3 in sIBM. HBD-3 showed characteristic intracellular accumulations near deposits of β-amyloid, LC3 and TLR3 in sIBM, and was detected in inflammatory infiltrations and macrophages invading necrotic muscle fibres in both IIM. The characteristic intracellular localization of HBD-3 near markers of degeneration and autophagy, and overexpression of endosomal TLR3 in sIBM hint at different pathogenetic mechanisms in sIBM compared with PM. This descriptive study serves as a first approach to the role of the innate immune system in sIBM and PM.